Vakarų Europos literatūros knygynai prieškariniame Kaune - Glosienė, Audronė (Knygotyra, 1995)
The article reveals some aspects of the history of booktrade in the year 1918–1940 in Lithuania. An attempt is made to show the ways of distributing the Western literature in Lithuania. There were two agencies of Western literature in temporary capital of independent Lithuania Kaunas – Pribačis and Vokiečių (Deutche Buchhandlung) book-shops. Both were owned by Lithuanian citizens of German nationality. The owner of Pribačis book-shop was Max Holzman and Vokiečių book-shop belonged to Valter Fišer. Two bookshops, situated in the very center of the city, were famous and popular among Lithuanian artists, scientists, writers, students. The circle of the book-shops’ clients is revealed in the article paying special attention to the professors and lectures of Kaunas university. They had possibility to look through the newest bibliographies, pamphlets and prospectus of Western publishers, to order books and periodicals from Germany, Austria, Switzerland and other countries, to get acquainted with last issues and to obtain them and old ones as well. Pribačis and Vokiečių book-shops had regular contacts with professors L. Karsavin, I. Jonynas, Z. Ivinskis, V. Biržiška and others. The new archival data is explored in the article to show the role of Pribačis and Vokiečių book-shops in supplying the academic society with Western literature necessary for researches, lecturing and reading. The book-shops also published several books in Lithuanian, German, English and French (text-books and reading books, studies in Lithuanian history, economics, politics, translation and anthologies of Lithuanian folk-songs and fiction). One of the most valuable publications was the study “The Art of Vilnius” by M. Vorobjov. The cooperation between Lithuanian libraries and book-shops of Western literature is also mentioned. The activities of Pribačis and Vokiečių book-shops are considered to be significant not only because of their succesful book-trade but also due to the high level of services and book-advertizing. Their excellent example influenced other Lithuanian book-sellers.